Tannin-furanic foams used as biomaterial substrates for SERS sensing in possible wastewater filter applications. (23rd November 2021) - Sabathi, Gebhard; Reyer, Andreas; Cefarin, Nicola; Sepperer, Thomas; Eckardt, Jonas; Neubauer, Jonas; Jan Wendisch, Fedja; D'Amico, Francesco; Vaccari, Lisa; Tondi, Gianluca; Musso, Maurizio
Abstract: Simple substrates for surface enhanced Raman spectroscopy (SERS), producible in a cost-efficient way, are of growing interest both for scientific and for environmental applications. In this study, we demonstrate the use of three types of bio-based tannin-furanic rigid foams as precursor materials for SERS substrates. Coated with a silver layer, these substrates allowed the detection of several well-known analytes in the mM regime by Raman spectroscopy. Specific optimization of the standard tannin-furanic foam morphology by tuning the chemical synthesis led to a smaller and more homogeneously distributed pore structure, supplying more active hot spot areas. Thus, we obtained a significant increase and a lower relative standard deviation (RSD) of the SERS signal recorded over the mapped SERS substrate area, for several analytes, in particular for Malachite Green dye. This work represents a feasibility study opening several potential applications of this biopolymers in fields such as the detection of water pollutants, virtually combining filtration and SERS capabilities driven by a controlled porosity.